FLUID THERAPY AND VASOPRESSOR SELECTION ALGORITHM IN THE MANAGEMENT OF SEPTIC SHOCK IN CHILDREN - Sharipov Behruz Rashidovich,; Pulatova Shahnoza Haydarovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Septic shock remains one of the most life-threatening emergencies in pediatric intensive  care,  characterized  by  impaired  perfusion,  cellular  dysfunction,  and  high mortality. The success of treatment depends heavily on early recognition, timely fluid resuscitation, and appropriate selection of vasopressor support. Unlike adults, children frequently present with cold shock, making therapeutic strategies uniquely pediatric-oriented.